Prodromus of a fern flora for Bolivia. XXXIV. Didymochlaenaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2018)
We provide a synopsis to the family Didymochlaenaceae in Bolivia, comprising the single pantropical species, Didymochlaena truncatula.